Determinants of self-medication with NSAIDs in a Portuguese community pharmacy - Nunes AP; Costa IM; Costa FA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Non-steroid anti-inflammatory drugs (NSAIDs) are a widely used therapeutic group in the world, and particularly in the Portuguese population. Objective: To compare NSAID's use by prescription and self-medication acquisition and to determine the pattern of indication of NSAIDs, their usage profile and possible implications for patients' safety. Methods: A cross-sectional design was used where individuals presenting at a community pharmacy requesting NSAIDs during the study period (one month) were invited to answer a face-to-face interview where socio-demographic characteristics, the indication pattern and previous experience of side effects were assessed. A follow-up interview was performed one week later to assess the incidence of adverse effects. The study was ethically approved. Results: A sample of 130 NSAIDs users was recruited, comprising mostly women (n=87; 66.9%), actively employed (n=77; 59.2%) and presenting a mean age of 49.5 years old (SD=20.49). An equal proportion of individuals acquired NSAIDs by self-medication and with medical prescription (n=65; 50%). Over 4/5 of patients (n=57; 87.7%) acquiring NSAIDs without a prescription were self-medicated by their own initiative, and only 10.8% (n=7) had been advised by the pharmacist. The most commonly acquired active substances were ibuprofen and diclofenac. Self-medicated users more frequently resorted to topical NSAIDs following short term treatments. The major underlying condition motivating NSAIDs sought were musculoskeletal disorders (45.0%), regardless of the regimen. An important proportion of prevalent users of NSAIDs reported previous experience of adverse effects (11.3%). One week after initiating NSAID therapy, a small proportion of patients reported incidence of adverse effects. Conclusion: Self-medication with NSAIDs is sought for numerous medical conditions. Reported adverse effects (prevalent and incident) confirm the need for a more rational use of NSAIDs and ongoing pharmacovigilance.